A DUAL-METHOD RISK MANAGEMENT FRAMEWORK FOR COAL-TO-SNG PROJECTS: EVIDENCE FROM INDONESIA’S STATE-OWNED ENERGY SECTOR - Latif Alfiyan Zuhri; Yunieta Anny Nainggolan (Journal of Economic, Bussines and Accounting (COSTING), 2026)
PT Bukit Asam Tbk (PTBA) faces challenges regarding the global decline in coal demand and price as well as stricter environmental regulation. To sustain its business, PTBA is initiating Coal to Synthetic Natural Gas (SNG) project as part of business diversification strategy. However, the project faces challenges and uncertainties. This study explores the risks associated with the project by using a dual method approach of Risk Matrix and Analytical Hierarchy Process (AHP) through interviews and questionnaires. A total of 38 risks were identified associated with the project across several categories. Seven top priority risks were highlighted including policy/regulatory uncertainty, geopolitical instability, technology selection, difficulties in project funding, LNG price decline, violation of good corporate governance (GCG), as well as licensing delays. The study found that different methods may provide different perspectives, due to the subjective nature of Risk Matrix as qualitative approach based on likelihood and consequence versus AHP which is more quantitative based on pairwise comparison weighting. The combination of both methods enhances the accuracy and reliability of the analysis in accordance with the principles of ISO 31000:2018. This study contributes theoretically by presenting a replicable dual-method approach of Risk Matrix (qualitative) and Analytical Hierarchy Process (quantitative) within the ISO 31000:2018 framework that can be adapted in similar projects, especially coal downstream or energy transition projects.